2019
DOI: 10.5578/turkjsurg.4204
|View full text |Cite
|
Sign up to set email alerts
|

Single-stage treatment with ERCP and laparoscopic cholecystectomy versus two-stage treatment with ERCP followed by laparoscopic cholecystectomy within six to eight weeks: a retrospective study

Abstract: Cite this article as: Muhammedoğlu B. Single-stage treatment with ERCP and laparoscopic cholecystectomy versus two-stage treatment with ERCP followed by laparoscopic cholecystectomy within 6 to 8 weeks: A retrospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
(15 reference statements)
1
3
1
Order By: Relevance
“…According to the operative data, there was statistically significant difference between the two groups regarding number of ERCP and anesthesia sessions as it was significantly higher in group (B) (p<0.001). In contrast with our results the study of (Muhammedoğlu, 2019) [7] which was done on Of the 350 patients undergoing ERCP between 01.01.2015 and 31.12.2016, 31 patients with single-stage ERCP and LC were assigned to Group A and 25 patients with two-stage ERCP followed by LC within 6-8 weeks were assigned to Group B, reported that Total duration of anesthesia did not differ statistically significantly between the study groups (154.06 ± 53.76 min in our Group A series and 167.04 ± 75.17 min in our Group B series).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…According to the operative data, there was statistically significant difference between the two groups regarding number of ERCP and anesthesia sessions as it was significantly higher in group (B) (p<0.001). In contrast with our results the study of (Muhammedoğlu, 2019) [7] which was done on Of the 350 patients undergoing ERCP between 01.01.2015 and 31.12.2016, 31 patients with single-stage ERCP and LC were assigned to Group A and 25 patients with two-stage ERCP followed by LC within 6-8 weeks were assigned to Group B, reported that Total duration of anesthesia did not differ statistically significantly between the study groups (154.06 ± 53.76 min in our Group A series and 167.04 ± 75.17 min in our Group B series).…”
Section: Discussioncontrasting
confidence: 99%
“…According to the Comparison of duration of hospital stay between the studied groups, our study showed that the mean duration of hospital stay in group (A) was 2.0± 1.78 days and 7.0± 3.53 days in group (B)s. Group (A) showed significant decrease in duration of hospital stay compared to group (B) (p<0.001). The study of (Vttoretto N et al, 2018 ) [13] support our results as it reported that the length of hospital stay appeared to be lowered in laparoendoscopic rendezvous group by aboutn three days, The study of (Muhammedoğlu, 2019) [7] supported our results as they reported that single-stage ERCP/LC is associated with shorter hospital stay. According to the Comparison of postoperative complications between the studied groups, our results showed that Two patients in group (A) had complications as they reported pancreatitis while 13 patients in group (B) showed postoperative complications.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Similarly, many studies found that the interval between ERCP and LC had no correlation with the length of LC procedures. [13,[16][17][18] The length of procedures varies based on the severity of diseases, medical equipment, and surgeons' experience. However, it also reflects the difficulty of procedures to a certain extent.…”
Section: Discussionmentioning
confidence: 99%